European Society of Endocrinology Clinical Practice Guideline for long-term follow-up of patients operated on for a phaeochromocytoma or a paraganglioma - Plouin, P F; Amar, L; Dekkers, O M; Fassnacht, M; Gimenez-Roqueplo, A P; Lenders, J W M; Lussey-Lepoutre, C; Steichen, O (European journal of endocrinology, 2016)
Phaeochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumours. Standard treatment is surgical resection. Following complete resection of the primary tumour, patients with PPGL are at risk of developing new tumoural events. The present guideline aims to propose standardised clinical care of long-term follow-up in patients operated on for a PPGL. The guideline has been developed by The European Society of Endocrinology and based on the Grading of Recommendations Assessment, Development and Evaluation (GRADE) principles. We performed a systematic review of the literature and analysed the European Network for the Study of Adrenal Tumours (ENS@T) database. The risk of new events persisted in the long term and was higher for patients with genetic or syndromic diseases. Follow-up in the published cohorts and in the ENS@T database was neither standardised nor exhaustive, resulting in a risk of follow-up bias and in low statistical power beyond 10 years after complete surgery. To inform patients and care providers in this context of low-quality evidence, the Guideline Working Group therefore prepared recommendations on the basis of expert consensus. Key recommendations are the following: we recommend that all patients with PPGL be considered for genetic testing; we recommend assaying plasma or urinary metanephrines every year to screen for local or metastatic recurrences or new tumours; and we suggest follow-up for at least 10 years in all patients operated on for a PPGL. High-risk patients (young patients and those with a genetic disease, a large tumour and/or a paraganglioma) should be offered lifelong annual follow-up.